The Dynamics of Adoptive Fathers as Marriage Guardians in Contemporary Studies - Fatima Zahara; Sukiati Sukiati (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2024)
Ulema assert that adopting fathers are not categorized as mahram elligible to be marital guardians (wali). However, Balige Religious Court Decision No.13/Pdt.P/2020/PA.Blg has legalized such marriage. This study aims to analyze considerations of the judge beyond the decision. This normative legal research employed encompass statutory, case-based, comparative, and conceptual analyses. The findings of this study indicate that marriages wherein the adopting father assuming the role as the marriage guardian for the prospective bride may be considered invalid. In accordance with Islamic legal norms, the guardian of marriage typically consists of wali nasab (biological guardians) of the prospective bride. In instances where no guardian of aqrab or wali ab'ad is available, the judge guardian assumes this responsibility. However, the adopting father does not fall within the purview of marriage guardianship. Nonetheless, in certain scenarios, such as that delineated in the decision, the applicant (wife), being a muallaf (new converts), lacks a Muslim guardian, while a trusted Muslim authority in the locale, such as the mosque's imam or a respected qadi, is found to be his adopting father. In this specific instance, the adopting father fulfills the role of a religious figure within the community. Referring him as a local religious authority holder in this context is more appropriate due to his social role than as the adopting father at his family circle. Consequently, this marriage is deemed valid and the court's decision aligns with the Islamic jurisprudence